Complementary feeding practices of children aged 6-23 months in rural area, Southern-Benin: challenges and opportunities - Mitchodigni, I.M.; Hounkpatin, Waliou Amoussa; Ntandou-Bouzitou, Gervais D.; Termote, Céline; Kennedy, G.; Hounhouigan, Djidjoho J. (Sciencedomain International, 2017)
Aims: This study aims to provide in-depth knowledge of current infant feeding practices in order to create an evidence base and develop well-targeted strategies to reduce the prevalence of child malnutrition.